KINERJA PEGAWAI YANG DIMODERASI KERAGAMAN KETERAMPILAN (Studi Kasus Pada Guru SLTA di Kota Semarang) - Widowati, Maduretno; Luhgiatno, Luhgiatno; Mohklas, Mohklas (STIE PENA, 2025)
This research aims to analyze the influence of self-efficacy and extensive training on employee performance, as well as to examine the moderating role of skill variety in these relationships. The research method employed is quantitative with a survey approach. Data were collected through questionnaires distributed to senior high school (SLTA) teachers in Semarang City and analyzed using partial hypothesis testing and moderation regression analysis techniques. The research results indicate that self-efficacy and extensive training have a positive and significant effect on employee performance. Furthermore, skill variety strengthens the relationship between self-efficacy and extensive training on performance. These findings suggest that organizations need to pay attention to the development of self-efficacy and provide comprehensive training, as well as encourage skill variety to optimize employee performance.Keywords: Self-Efficacy, Extensive Training, Employee Performance, and Skill Variety.